RIST: A potent new combination therapy for glioblastoma. Issue 4 (1st September 2014) - Nonnenmacher, Lisa; Westhoff, Mike‐Andrew; Fulda, Simone; Karpel‐Massler, Georg; Halatsch, Marc‐Eric; Engelke, Jens; Simmet, Thomas; Corbacioglu, Selim; Debatin, Klaus‐Michael
<x xml:space="preserve">Abstract</x> Glioblastoma is a highly aggressive, common brain tumor with poor prognosis. Therefore, this study examines a new therapeutic approach targeting oncogenic and survival pathways combined with common chemotherapeutics. The RIST (rapamycin, irinotecan, sunitinib, temozolomide) and the variant aRIST (alternative to rapamycin, GDC‐0941) therapy delineate growth inhibiting effects in established glioblastoma cell lines and primary cultured patient material. These combinations significantly decreased cell numbers and viability compared to inhibitors and chemotherapeutics alone with aRIST being superior to RIST. Notably, RIST/aRIST appeared to be apoptogenic evoked by reduction of anti‐apoptotic protein levels of XIAP and BCL‐2, with concomitant up‐regulation of pro‐apoptotic protein levels of p53 and BAX. The treatment success of RIST therapy was confirmed in an orthotopic mouse model. This combination treatment revealed significantly prolonged survival time and drastically reduced the tumor burden by acting anti‐proliferative and pro‐apoptotic. Surprisingly, in vivo, aRIST only marginally extended survival time with tumor volumes comparable to controls. We found that aRIST down‐regulates the microvessel density suggesting an insufficient distribution of chemotherapy. Further, alterations in different molecular modes of action in vivo than in vitro suggest, that in vivo RIST therapy may mimic the superior aRIST protocol's pro‐apoptotic inhibition of pAKT in vitro. Of note, all substances were administered in therapeutically relevant low doses with no adverse side effects observed. We also provide evidence of the potential benefits of the RIST therapy in a clinical setting. Our data indicates RIST therapy as a novel treatment strategy for glioblastoma achieving significant anti‐tumorigenic activity avoiding high‐dose chemotherapy.